Modelling OpenComRTOS tasks interaction - Mezhuyev, V.; Verhulst, E. (Математичні машини і системи, 2010)
The model of tasks interaction in Open Communication Real Time Operation System (OpenComRTOS) is developed and discussed in the paper. The main feature of the proposed approach is the using the intermediate hub entity for decoupling interacting tasks. Different temporal semantics (waiting, non waiting and waiting timeout) of tasks synchronization mechanism is introduced. Emerging the effects (i.e. synchronisation or the absence of it) in the case when the tasks actions have different temporal semantics is analysed. The different approaches for expanding the hub model with using TLA and Hoare triplets are proposed.